Isolation and Identification of Pathogenic Fungi from Cyprinus carpio L. (1758) in Al-Nasiriya City - Ihsan Flayyih Hasan AI-Jawhari (Journal of Global Pharma Technology, 2016)
Thirty  samples  of  Cyprinus  carpio  were   collected  from Al-Nasiriya fish  ponds  during  the  period  from  March   until  Novmber  2017 . Seventeen  fish  samples  showed  fungal  infection .In this study eight species were identified and the most common were Aspergillus  niger, Saplolegnia sp., Achyla  prolifera, Alternaria  alternate , Penicillium funigulosum, Rhizopus  stolinifer, Aspergillus  fumigatus and  Aspergillus  flavus . Aspergillus Niger and Saplolegnia sp. were the most prevalent fungi infecting all the organs of Cyprinus carpio. Gills  and  abdomen   had  higher  infection  than  rest  of  the  organs .Keywords: Contaminnet, Disease, Environment, Fishes, Fungi, Ponds.